La difficile réintégration d’une communauté religieuse et la création d’une société biconfessionnelle : l’espace de la Fête-Dieu à Montauban au XVIIe siècle - Danny Bertrand (Les Cahiers de Framespa)
This article examines the way in which the general procession during the celebration of Corpus Christi reveals the challenges linked to the realities of religious coexistence after the adoption of the Edict of Nantes by the government of King Henry IV. The reestablishment of this public ceremony provoked a confrontation opposing the municipal council and the bishop of Montauban. Its reoccurrence in 1607 opened a breach and allowed the Catholics to reclaim the urban space which had been dominated and controlled by the Calvinists since 1561.